2010
DOI: 10.3155/1047-3289.60.10.1262
|View full text |Cite
|
Sign up to set email alerts
|

Fugitive Dust Emission Source Profiles and Assessment of Selected Control Strategies for Particulate Matter at Gravel Processing Sites in Taiwan

Abstract: Particles emitted from gravel processing sites are one contributor to worsening air quality in Taiwan. Major pollution sources at gravel processing sites include gravel and sand piles, unpaved roads, material crushers, and bare ground. This study analyzed fugitive dust emission characteristics at each pollution source using several types of particle samplers, including total suspended particulates (TSP), suspended particulate (PM10), fine suspended particulate (PM2.5), particulate sizer, and dust-fall collecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…TSP source mass concentration was same order of magnitude, approximately 1100 µg/m 3 and 3500 µg/m 3 , also in studies conducted in Taiwan and Nigeria, respectively [20,42]. The lowest TSP source concentrations were measured at a gravel crushing site [43] and at a limestone mine and a granite quarry [3]. Both studies measured TSP mass concentration approximately from 100 to 1000 µg/m 3 .…”
Section: Dust Formed During the Drilling Crushing And Haulingsupporting
confidence: 61%
See 1 more Smart Citation
“…TSP source mass concentration was same order of magnitude, approximately 1100 µg/m 3 and 3500 µg/m 3 , also in studies conducted in Taiwan and Nigeria, respectively [20,42]. The lowest TSP source concentrations were measured at a gravel crushing site [43] and at a limestone mine and a granite quarry [3]. Both studies measured TSP mass concentration approximately from 100 to 1000 µg/m 3 .…”
Section: Dust Formed During the Drilling Crushing And Haulingsupporting
confidence: 61%
“…Degan et al [44] gained PM10 concentrations approximately 4400 µg/m 3 and 5400 µg/m 3 for primary and secondary crushing, respectively. Other researches gained lower PM10 mass concentrations, roughly 1000 µg/m 3 [20,51,52] or only few hundred µg PM10/m 3 [3,42,43].…”
Section: Dust Formed During the Drilling Crushing And Haulingmentioning
confidence: 99%
“…Figs. 1 and 2 show the locations of the sampling sites at the two facilities, which are similar to hundreds of sand and gravel operations throughout the world (Richards and Palm, 2000;Lee et al, 2001;Shiraki and Holmen, 2002;Chang, 2006;Trzepla-Nabaglo et al, 2006;Semple et al, 2008;Pimonsree et al, 2009;Richards et al, 2009;Chang et al, 2010) that support asphalt and concrete construction projects.…”
Section: Methodsmentioning
confidence: 99%
“…PM 10 consists of many particle sizes with different deposition velocities (McMahon and Denison, 1979;Sehmel, 1980) that can cause large gradients in downwind concentration with distance from the emitters. Shortduration emissions of large particles from a nearby source within or outside the facility may dominate the integrated PM concentration , while PM concentrations reduce exponentially with increased distance from fugitive dust sources (Lee et al, 2001;Tsai and Chang, 2002;Chang, 2004Chang, , 2006Chang et al, 2010). Although the hivol size-selective inlet (SSI) sampler is a U.S. EPA Federal Reference Method (FRM) for TSP and PM 10 (U.S. EPA, 2011), it requires a large footprint and line power, making it difficult to locate in appropriate sampling sites.…”
Section: Introductionmentioning
confidence: 99%
“…A researcher captured the image of dust fugitively emitted from the dry ephemeral river valleys along the Namibian coast by adopting photography and imagery skills (Eckardt et al, 2005). Other researchers found that the total suspended particulate emissions from dry land basins were highly related to several affecting factors (e.g., air temperature, soil silt content, and wind speed) (Lin et al, 2007;Chang et al, 2011;Syu et al, 2016). Taiwan Environmental Protection Administration (TEPA) reported that aeolian dust were the dominant air pollutants in the estuaries of major rivers of central Taiwan in winter (Taiwan EPA, 2009).…”
Section: Introductionmentioning
confidence: 99%